A review of the reproductive habitat preferences and conservation challenges of a rare, transient, and ecologically restricted darner dragonfly: Rhionaeschna mutata. Issue 1 (2nd January 2019) - Schilling, Emily Gaenzle; Lawrenz, Ron; Kundel, Holly
Abstract : Rhionaeschna mutata is a rare North American dragonfly that is considered a species of concern or threatened throughout its range. It is most widely distributed in the eastern USA, but recent adult records indicate that its range extends further north and west than previously known. Effective conservation planning for rare species requires understanding their habitat requirements, and no comprehensive characterization of this species' reproductive habitat has previously been conducted. We conducted a review to synthesize information from records throughout this species' range and identified a narrow set of conditions that describe R. mutata reproductive habitat: small, heavily vegetated, fish-free ponds with a wooded riparian edge and with sphagnum present. While this habitat type may formerly have been widespread across this species' native range, anthropogenic activities have likely resulted in loss and increased fragmentation of R. mutata reproductive habitat. Our review also revealed that this species is transient or ephemeral, collected at a site one year and absent in subsequent years. Effective conservation planning for ecologically restricted odonates, such as R. mutata, requires consideration of multiple anthropogenic activities that threaten species' ability to persist.